TKSE: Trustworthy Keyword Search Over Encrypted Data With Two-Side Verifiability via Blockchain - Yinghui Zhang; Robert H. Deng; Jiangang Shu; Kan Yang; Dong Zheng (IEEE Access, 2018)
As a very attractive computing paradigm, cloud computing makes it possible for resource-constrained users to enjoy cost-effective and flexible resources of diversity. Considering the untrustworthiness of cloud servers and the data privacy of users, it is necessary to encrypt the data before outsourcing it to the cloud. However, the form of encrypted storage also poses a series of problems, such as: How can users search over the outsourced data? How to realize user-side verifiability of search results to resist malicious cloud servers? How to enable server-side verifiability of outsourced data to check malicious data owners? How to achieve payment fairness between the user and the cloud without introducing any third party? Towards addressing these challenging issues, in this paper, we introduce TKSE, a trustworthy keyword search scheme over encrypted data without any third party, trusted or not. In TKSE, the encrypted data index based on digital signature allows a user to search over the outsourced encrypted data and check whether the search result returned by the cloud fulfills the pre-specified search requirements. In particular, for the first time, TKSE realizes server-side verifiability which protects honest cloud servers from being framed by malicious data owners in the data storage phase. Furthermore, blockchain technologies and hash functions are used to enable payment fairness of search fees without introducing any third party even if the user or the cloud is malicious. Our security analysis and performance evaluation indicate that TKSE is secure and efficient and it is suitable for cloud computing.